Gene silencing approaches for the management of dyslipidaemia - Norata, Giuseppe; Tibolla, G.; Catapano, A. (2013)
The key role of dyslipidaemias in determining cardiovascular risk has been well established, and statins often provide effective therapeutic management. However, many patients do not achieve recommended lipid levels despite maximal therapy, and some cannot tolerate high-dose statin therapy. Recently, genetic insights into mechanisms underlying regulation of lipoprotein metabolism have expanded the potential targets of drug therapy and led to the development of novel agents, including development of gene silencing approaches. These therapeutic options include the modulation of synthesis in the liver, maturation in the circulation, and catabolism of lipoproteins. In this review, we discuss the pharmacological consequences of silencing apolipoprotein B, apolipoprotein (a), microRNA 33, proprotein convertase subtilisin/kexin type 9, and apolipoprotein C-III. New potential targets such as other microRNAs, diacylglycerol acyl transferase-1, and angiopoietin-like protein 3 are also presented. The pharmacological consequences of gene silencing and the advancement of these therapeutic approaches in clinical development will be examined. © 2013 Elsevier Ltd.